Pengaruh Layanan Bimbingan Kelompok Terhadap Perencanaan Arah Karier Siswa SMA Pembangunan Laboratorium Universitas Negeri Padang - Nengsih, Nengsih; Firman, Firman; Iswari, Mega (Konselor, 2015)
Planning career direction is a dynamic process and systematically assist students in determining the path of further education or work aspired. A phenomenon that occurs student is not realistic in choosing further education, are not ready to choose further education, and confused in choosing colleges and majors who wish to enter. One of the services that can be used to help students planning a career direction is a group counseling services. This study aims to reveal (1) planning career direction experimental group before and after being given treatment, (2) planning career direction control group pre-test and post-test without being offered treatment (3) planning towards student careers experimental and control groups in post -test.The method used in this research is a quasi-experimental research design nonequivalent control group design. The population in this study were students of class XI SMA Development Laboratory State University of Padang and SMA Pertiwi 1 Padang. Sampling by random sampling technique. The research sample numbering 20 students. The instrument used is a Likert scale model. Data were analyzed using non-parametric statistics using the Wilcoxon Signed Ranks Test and Kolmogorov-Smirnov 2 Independent Samples with SPSS version 20.00.The findings of this s research in general that guidance services group influence on the planning direction student careers, whereas in particular: (1) there are significant differences planning career direction before and after following guidance services group, (2) there are no significant differences planning career direction the control group pre-test and post-test without a given treatment, and (3) there is a significant difference toward career planning students experimental and control groups in post-test. Based on the above findings, it can be concluded that students planning a career direction can be enhanced with group counseling services.Â